(untitled) (LACCEI, 2024)
The main objective of the study was to improve the service level of a distribution and marketing company, surpassing the 93.19% indicator recorded in 2021 and reaching a service level of over 95%. The improvement proposal focused on reducing dispatch process times, reducing quality errors in the products delivered to the client and improving merchandise control. To achieve these objectives, Lean Warehousing, inventory management and Systematic Layout Planning methodologies were applied, resulting in a more efficient warehouse system. As a result, the monthly average time of the dispatch process was reduced from 574.20 to 429.12 minutes, the daily cases of damaged or broken merchandise were reduced by 75%, and there was a total improvement in the cases of expired or soon-to-expire products. In addition, merchandise control improved from 87% to 98.64% according to the ERI, and there was a 62.63% decrease in costs for total and partial returns, compared to annual losses of S/1,569,859.28 before the improvement. It should be noted that during the application of the methodologies, it was found that implementation takes time and requires adequate training of personnel.